PELAKSANAAN PENDIDIKAN KARAKTER DI M.I. MIFTAHUL ULUM TAMBAKREJO TONGAS PROBOLINGGO - Nur Khosiah (Ar-Risalah Media Keislaman Pendidikan dan Hukum Islam, 2019)
This research aims to study the value, the policy, the design, and also the application of character building education in Miftahul Ulum tambakrejo elementary school. The character building in Miftahul Ulum Tambakrejo elementary school consists of religious value beside independence and careness. In order the policy to be successful, the character building includes three points: 1) about learning such as giving more time for religion subjects, 2) the capacity building for teacher, 3) outside class activity such as supplying ÃƒÂ¢Ã¢â€šÂ¬Ã…â€œmy diaryÃƒÂ¢Ã¢â€šÂ¬Ã‚Â book. The character building education in Miftahul Ulum Tambakrejo elementary school was applied inside and the classroom. The activity inside the classroom was applied with integrated model and strategy, namely integrated all the subjects with character value and related to the character in daily life. Meanwhile the approach used is inculcation approach. It is an approach that uses example in learning procces such as warshipping activities in the school. The character building outside the classroom was applied by having outbound, outdoor, extracurricular and worshipping custom. These activities will then be a good habit, so that the students always do positive thing.